Determination of aminopolycarboxylate complexes of transition metal (Mn²⁺, Cu²⁺ and Fe³⁺) in pulp by capillary zone electrophoresis (CZE-DAD) - Goje Tesfai, Tedros (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc)--Stellenbosch University, 2004.